Computational design of a metallic VS₂/N-doped graphene nanocomposite anode for multivalent metal-ion batteries - Hassan, Ahmed Jaber; Tim, Chan Kar; Pah, Lim Kean; Mohd Shah, Nurisya; Halim, Umair Abdul; Mohd Noor, Nurfarhana; Abdul Razak, Wan Mohammad Zulkarnain (Springer, 2026)
The rational design of advanced anode materials is central to overcoming the limitations of conventional lithium-, sodium-, and magnesium-ion batteries. Here, we propose and systematically investigate a novel VS₂/nitrogen-doped graphene (VS₂/NGr) nanocomposite using density functional theory (DFT). The heterostructure exhibits a negative formation energy (− 0.025 eV), confirming thermodynamic stability, while nitrogen doping enhances interfacial coupling and charge redistribution. Electronic analysis reveals intrinsic metallic conductivity, and mechanical simulations demonstrate outstanding 2D stiffness (502.9 N/m) and stretchability, ensuring robustness during cycling. Electrochemical evaluations demonstrate strong ion adsorption and ultralow diffusion barriers of 0.16 eV (Li⁺, Na⁺) and 0.32 eV (Mg2⁺), enabling rapid and selective ion transport. The system achieves average open-circuit voltages of 0.70 V (Li), 0.55 V (Na), and 0.15 V (Mg), with corresponding theoretical specific capacities of 1153, 961, and 1922 mA·h·g⁻1, respectively. These results demonstrate superior performance compared to pristine VS₂, graphene, and many reported 2D heterostructures. Collectively, these findings position VS₂/NGr as a robust, high-capacity, and rate-capable anode, and highlight heteroatom doping and van der Waals engineering as effective strategies for designing next-generation energy storage systems.